PERBANDINGAN PENINGKATAN KEMAMPUAN KONEKSI MATEMATIS SISWA SMA YANG MEMPEROLEH PEMBELAJARAN MODEL DISCOVERY LEARNING DAN MODEL ELICITING ACTIVITIES (MEAs) - Nisa Siti Solehah, - (2019)
"The Comparison in the Improvement of Mathematical Connection Ability of High School Students who acquired Model Discovery Learning and Model Eliciting Activities (MEAs)" Nisa Siti Solehah (1505028) Mathematics Education Study Program. Faculty of Mathematics and Natural Science Education. Universitas Pendidikan Indonesia (UPI) This research aimed to investigate the difference and the comparison in the improvement of mathematical connection ability of high school students who acquired Model Discovery Learning and Model Eliciting Activities (MEAs) based on Kemampuan Awal Matematis (KAM). The research design of this study was the pretest posttest two treatment design. The population of this research was students from one of the senior high schools at Karawang. The samples of this study consisted of two groups: first group with 36 people and Eliciting Activities Model, second class with 36 people with Discovery Learning Model. From this research, it can be concluded that there were a distinction in the improvement and achievement of mathematical connection ability of high school students who acquired Model Discovery Learning and Model Eliciting Activities (MEAs). However, there was no distinction in the improvement of mathematical connection ability of high school students who acquired Model Discovery Learning and Model Eliciting Activities (MEAs) based on the view of Kemampuan Awal Matematis (KAM)-the initial mathematical ability of high, medium, and low. Keywords : Model Discovery Learning, Model Eliciting Activities, mathematical connection